Comparison of Antioxidant Activity, Total Phenolic, Flavonoid, Proanthocyanidin, Saponin Contents of Eggplant’s (Solanum Melongena l.) Pulp and Peel – a Chemometric Approach - MITIĆ, Violeta D.; NIKOLIĆ, Jelena S.; DIMITRIJEVIĆ, Marija V.; MRMOŠANIN, Jelena M.; TOŠIĆ, Snežana B.; PAVLOVIĆ, Aleksandra N.; STANKOV JOVANOVIĆ, Vesna P. (Studia Universitatis Babeș-Bolyai Chemia, 2023)
The eggplant is a vegetable that has been used more in recent years thanks to the low calories versus high content of phenolic compounds. This study aimed to determine total phenolic, flavonoid, proanthocyanidin, and saponin content using spectrophotometric assays and antioxidant activity using 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), 2,2’-azinobis(3-ethylbenzothiazol-6sulpho-nate (ABTS), total reducing power (TRP), ferric reducing antioxidant power (FRAP), and cupric reducing antioxidant capacity (CUPRAC) assassin peel and pulp of eggplant cultivars Robi, Tudela, Vernal, Aragon, and Rosa Bianca. The average total saponin content (TSC) in peel was 116.34 µg DSGE mg-1 DW (diosgenin equivalents per mg of extract’s dry weight), whereas in pulp was slightly lower (107.86 µg DSGE mg-1 DW). A similar trend was observed for total phenolic content (TPC) (24.54 µg GAE mg-1 DW (gallic acid equivalents per mg of extract’s dry weight) in peel and 15.88 µg GAE mg-1 DW in pulp); total proanthocyanidin (TP) (2.74 µg CE mg-1 DW (catechin equivalents per mg of extract’s dry weight) in peel and 1.24 µg CE mg-1 DW in pulp) and total flavonoid content (TFC) (0,05 µg RE mg-1 DW (rutin equivalents per mg of extract’s dry weight) in peel and 0.02 µg RE mg-1 DW in pulp). Principal component analysis (PCA) and cluster analysis (CA) methods were applied on the antioxidant activity (ABTS, DPPH, TRP, FRAP, and CUPRAC) and total bioactive compounds content (TSC, TPC, TP and TFC) parameters in order to reveal the relationships between analyzed samples. As a result of these approaches, analyzed samples were grouped into two groups.